(untitled) (De la Crítica, 2023)
The purpose of this research was to understand the meanings conferred by the teacher to the social values present in the written production of the 3rd-grade students of sections "A" and "B" of the UEE La Democracia, located in Maracay, Andrés Eloy Blanco Municipality, Aragua State. In order to make a diagnosis to know the writing levels of all the children of these sections and their relationship with social values. In the present investigation, the fundamental theoreticians that sustain the work are cited, such as Goodman, Lerner and Levy, Piaget, Vygotsky, Ferreiro and Teberosky, and Cassany, among others. The research is based on the qualitative-interpretative paradigm, under the phenomenological method with a field research type, and the researcher’s systematization diary instruments. A purposive sample of two third-grade teachers was used, one for each section. Likewise, by means of the semi-structured interview technique with the support of collection instruments, the information was obtained and categorized in individual matrices and codified using referential figures for its subsequent structuring. Subsequently, the categories were contrasted with the theoretical constructs and the researcher’s reflections, obtaining a result that the maximum social value of writing is communication. And among the findings we have, that the informants visualize writing as a process of expression of ideas, knowledge, etc., thus omitting that whoever writes does it to be read, which implies that he/she must have the receiver in mind.